How to make a deal: The role of rankings and personal ties in creating trust in the M&A market - Valérie Boussard; Olivier Godechot; Nicolas Woloszko (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2016)
This paper examines the selection of intermediaries in the French mergers and acquisitions (M&A) market, which is an opaque environment. Buyers and sellers cope with uncertainty as to the value of exchanged assets. They thus rely on the help of experts in order to secure deals. But as the valuators might be prone to opportunism, firms need to find a way to trust them. We identify two trust devices: social ties and public rankings. We explore whether these personal and impersonal devices are substitutes, independent or complementary. We study the French M&A market through a mixed-method approach, with both an ethnographic study (76 interviews) and the statistical analysis of 694 M&A deals in France in 2010. We show that both previous contacts and league table rankings of firms contribute to trust and to dealmaking. These trust devices are all the more likely to be used if the deal is risky, especially within the sell side (more at risk). We also find that firms tend to make deals only with other firms at the same level in the league tables: high-status firms tend to make deals together. Finally, we find some evidence of substitution between rankings and personal ties, especially for low-value deals.
Keywords: 330; financial market; mergers and acquisitions; network; rankings; trust; teams